2022
DOI: 10.5492/wjccm.v11.i4.298
|View full text |Cite
|
Sign up to set email alerts
|

Association between early viral lower respiratory tract infections and subsequent asthma development

Abstract: BACKGROUND The association between hospitalization for human respiratory syncytial virus (HRSV) bronchiolitis in early childhood and subsequent asthma is well established. The long-term prognosis for non-bronchiolitis lower respiratory tract infections (LRTI) caused by viruses different from HRSV and rhinovirus, on the other hand, has received less interest. AIM To investigate the relationship between infant LRTI and later asthma and examine the influence of confounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…The immune response of the body after RSV infections in infants and children, along with the influence of neuromodulatory mechanisms and the persistence of RSV leading to adaptive remodeling of airway ultrastructure, may cause airway hyperresponsiveness, which is strongly associated with the development of recurrent wheezing and asthma later in life [ 155 158 ]. A recent review of 906 patients with asthma found that viral LRTIs in infants aged ≤ 2 years were associated with an increased risk of asthma for up to 20 years thereafter (odds ratio = 5.0; 95% confidence interval, 3.3–7.5), with RSV as the predominant pathogen (83.3%) [ 159 ]. Another prospective population-based cohort study showed that the prevalence of asthma at age 5 years was higher in children with RSV infections in infancy than in children without evidence of RSV infections in infancy (21% vs. 16%) [ 150 ].…”
Section: Resultsmentioning
confidence: 99%
“…The immune response of the body after RSV infections in infants and children, along with the influence of neuromodulatory mechanisms and the persistence of RSV leading to adaptive remodeling of airway ultrastructure, may cause airway hyperresponsiveness, which is strongly associated with the development of recurrent wheezing and asthma later in life [ 155 158 ]. A recent review of 906 patients with asthma found that viral LRTIs in infants aged ≤ 2 years were associated with an increased risk of asthma for up to 20 years thereafter (odds ratio = 5.0; 95% confidence interval, 3.3–7.5), with RSV as the predominant pathogen (83.3%) [ 159 ]. Another prospective population-based cohort study showed that the prevalence of asthma at age 5 years was higher in children with RSV infections in infancy than in children without evidence of RSV infections in infancy (21% vs. 16%) [ 150 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several other long-term and/or less frequent aspects need to be assessed after RSV prophylaxis implementation. For example, it is possible that early lower-respiratory-tract infection due to RSV could lead to asthma 35 or RSV infection could trigger invasive pneumococcal diseases. 36 Since March 2020, several nonpharmaceutical interventions have been implemented for the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RTIs are associated with preschool wheezing affecting up to 30% of children, and nearly 15%–25% of children experience recurrent wheezing before school age 9 . Viral RTIs are associated with a high level of inflammation and may contribute to airway remodeling 10 and to significantly increased risk of preschool recurrent wheezing and asthma later in life, 11–13 which may in turn have irreversible effects on lung function.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, RTIs are associated with preschool wheezing affecting up to 30% of children, and nearly 15%-25% of children experience recurrent wheezing before school age. 9 Viral RTIs are associated with a high level of inflammation and may contribute to airway remodeling 10 and to significantly increased risk of preschool recurrent wheezing and asthma later in life, [11][12][13] which may in turn have irreversible effects on lung function. Some consensus documents and statements recommend the use of immunostimulants to boost the body's natural defenses against infections and reduce the probability of reinfection in susceptible children.…”
mentioning
confidence: 99%